The immunologic effects of estrogen on psoriasis: A comprehensive review - Melissa Danesh, B.S; Jenny E. Murase, M.D (Wolters Kluwer, 2015)
Background: Immunological changes in pregnancy are associated with improvements in some pre-existing immune-mediated skin diseases. Estrogen has been hypothesized to contribute to these changes by creating a shift from Th1 and Th17 to Th2 immunity. As this hypothesis would predict, psoriasis (a primarily Th17 mediated immune disease) tends to improve during pregnancy. However, the precise mechanism by which estrogen induces immunological change in psoriasis remains poorly understood. Objective: To summarize the immunologic effects of estrogen as they relate to psoriasis during pregnancy. Methods: We performed an English-language PubMed search of articles from September 2004 to September 2014 combining the key terms ''psoriasis,'' ''estrogen,'' ''autoimmune disease,'' and ''pregnancy.'' Results: Estrogen appears to up-regulate Th2 cytokines and down-regulate Th1 and Th17 cytokines. This shift was initially observed in murine systems, which showed decreased mixed lymphocyte reactions of splenocytes and increased antibody production during pregnancy. Antigen stimulated splenocytes produced fewer Th1 cytokines and more Th2 cytokines in pregnant mice. IL17 producing T cells were significantly decreased in healthy pregnancies compared to non-pregnant controls. Limitations: This review is limited by the paucity of studies evaluating immunological changes of psoriasis in pregnancy among human subjects. Conclusions: Increased estrogen production in pregnancy is associated with decreased Th1 and Th17 cytokine production. While estrogen may be responsible for some of these immune shifts resulting in disease improvement, there remains no definitive evidence to prove the hypothesis that estrogen is responsible for such improvement. Keywords: psoriasis, pregnancy, estrogen, immunology